Emerging therapeutic approaches in graves’ ophthalmopathy: an update on pharmacological interventions - Lin Wang; Linlin Chen (Frontiers in Immunology, 2025)
Graves’ ophthalmopathy (GO), also known as thyroid eye disease (TED), is the most common extrathyroidal manifestation of Graves’ disease and a leading cause of visual morbidity. The disease primarily affects the orbital tissue and is characterized by inflammation, expansion of extraocular muscles, and remodeling of orbital fat, resulting in proptosis, diplopia, and even vision loss. Active GO poses significant therapeutic challenges and often requires prompt intervention to preserve visual function and improve quality of life. Over the past decade, considerable progress has been made in understanding the immunopathogenesis of GO, leading to the development of targeted pharmacological therapies that extend beyond traditional systemic corticosteroids. This review summarizes recent advances in the drug therapy of active GO, focusing on novel immunomodulators, biological agents such as monoclonal antibodies targeting CD20, IL-6 R, and insulin-like growth factor-1 receptor (IGF-1R), and evolving treatment strategies based on disease activity and severity. We also discuss current clinical practice guidelines, emerging therapeutic targets under investigation, and future perspectives in the individualized management of this vision-threatening autoimmune condition.